Growing up in Ancient Sardinia: Infant-toddler dietary changes revealed by the novel use of hydrogen isotopes (δ2H). - Saskia E Ryan; Linda M Reynard; Elisa Pompianu; Peter van Dommelen; Clizia Murgia; M Eulàlia Subirà; Noreen Tuross (PLoS ONE)
Detailed information about the lives and deaths of children in antiquity is often in short supply. Childhood dietary histories are, however, recorded and maintained in the teeth of both juveniles and adults. Primary tooth dentinal collagen does not turn over, preserving a sequential record of dietary changes. The use of nitrogen (δ15N) and carbon (δ13C) isotope values of incrementally sampled dentin are used in the study of breastfeeding practices but evidence for the addition of weaning foods, both in terms of mode and, particularly, duration, has remained analytically inaccessible to date. Here, we demonstrate how the novel use hydrogen isotope (δ2H) values of sequentially micro-sampled dentin collagen, measured from individuals excavated from a Punic cemetery, in Sardinia, Italy, can serve as a proxy for weaning food type and duration in ancient childhood diet. The weaning rate and age, based on the decline in δ15N and δ13C values of permanent first molars and the concomitant increase in δ2H, appears to be broadly similar among six individuals. Hydrogen isotopes vary systematically from a low value soon after birth, rising through early childhood. The early post-birth values can be explained by the influence of 2H-depleted lipids from mother's breastmilk and the later δ2H rise is consistent with, among other things, a substantial portion of boiled foodstuffs, such as the higher δ2H values observed in porridge. Overall δ2H in dentin shows great promise to elucidate infant and childhood feeding practices, and especially the introduction of supplementary foods during the weaning process.